Decarbonisation of the Transport Sector in Nigeria - Chidi E Akujor; Emmanuel E Uzowuru; Sambo S Abubakar; Chijioke M Amakom (SAGE Publishing, 2022)
We reviewed the various sub-sectors of the Nigerian transport sector with their corresponding energy consumption rates. Results show that all the sub-sectors are solely dependent on fossil fuels to meet their energy demands and requirements, thus making the transport sector the highest consumer of fossil fuels, and consequently, the highest contributor to carbon footprint. This necessitates the need for gradual decarbonisation of the sector, but not at the expense of the nation's economy, since the transport sector contributes about 3% of the nation's GDP. We have therefore outlined measures to decarbonise the sector. These include revitalisation of the rail and water transport; encouragement of mass transit; improving the state of security on Nigerian roads; employment of low-carbon fuels (biodiesels); and use of electric vehicles.